Post Pneumonectomy Bronchopleural Fistulae - Shah, Shahkar Ahmed; Bilal, Amir; Ahmed, Zahoor; Watson, D. (Journal of Postgraduate Medical Institute, 2011)
BPF remains one of the most dreaded and not an uncommon complication following penumonectomy. The results can be dramatically fatal, with the patient expiring within seconds, or it may manifest itself as a chronic debilaitating couhg and ill health. In either cases, BPF remains one of the major cases of mortlaity and morbidity following penumonectomy. An attempt is made here to identify the risk factors and suggest preventive measures by a retrospective analysis of pneumonectomies.